Interaction of defibrillation waveform with the time to defibrillation or the number of defibrillation attempts on survival from out-of-hospital cardiac arrest. (January 2018) - Hagihara, Akihito; Onozuka, Daisuke; Ono, Junko; Nagata, Takashi; Hasegawa, Manabu
Abstract: Aim: Early biphasic defibrillation is effective in out-of-hospital cardiac arrest (OHCA) cases. In the resuscitation of patients with OHCA, it is not clear how the defibrillation waveform interacts with the time to defibrillation to influence patient survival. The second, and any subsequent, shocks need to be administered by an on-line physician in Japan. Thus, we investigated the interaction between the defibrillation waveform and time to or the number of defibrillation on resuscitation outcomes. Methods: This prospective observational study used data for all OHCAs that occurred between 2005 and 2014 in Japan. To investigate the interaction effect between the defibrillation waveform and the time to defibrillation or the number of defibrillations on the return to spontaneous circulation (ROSC), 1-month survival, and cerebral performance category (CPC) (1, 2), we assessed the modifying effects of the defibrillation waveform and the time to or the number of defibrillation on additive scale ( i.e., the relative excessive risk due to interaction, RERI) and multiplicative scale ( i.e., ratio of odds ratios (ORs)). Results: In total, 71, 566 cases met the inclusion criteria. For the measure of interaction between the defibrillation waveform and the time to defibrillation, ratio of ORs for ROSC was 0.84 (0.75–0.94), implying that the effect of time to first defibrillation on ROSC was negatively modified by defibrillation waveform. For the interaction between the defibrillation waveform and the number of defibrillations, RERI and ratio of ORs for CPC (1, 2) was −0.25 (−0.47 to −0.06) and 0.79 (0.67–0.93), respectively. It is implied that the effect of number of defibrillation on CPC (1, 2) was negatively modified by defibrillation waveform. Conclusions: An increased number of defibrillations was associated with a decreased ROSC in the case of biphasic and monophasic defibrillation, while an increased number of defibrillations was related to an increased 1-month survival rate and CPC (1, 2) only in the case of biphasic defibrillation. When two or more defibrillations were performed, a biphasic waveform was more effective in terms of long-term survival than a monophasic waveform.